Klebsiella pneumoniae Lower Respiratory Tract Infection in a South African Birth Cohort: a Longitudinal Study - Heather J Zar; Rae MacGinty; Lesley Workman; Tiffany Burd; Gerald Smith; Landon Myer; Jonas Häggström; Mark P Nicol (International Journal of Infectious Diseases, 2022)
Objectives: The role of Klebsiella pneumoniae (KP) in lower respiratory tract infection (LRTI) is not well studied. We longitudinally investigated KP colonization and its association with LRTI in a South African birth cohort. Methods: We conducted a case-control study of infants who developed LRTI and age-matched controls, followed twice weekly through infancy. Nasopharyngeal swabs taken fortnightly and at LRTI for 33-multipex Quantitative multiplex real-time polymerase chain reaction were tested at LRTI and twice weekly from 90 days preceding LRTI. Controls were tested over the equivalent period. Multivariate models investigated the factors associated with LRTI or with KP-associated LRTI (KP-LRTI). Results: Among 885 infants, there were 439 LRTI episodes, of which 68 (15.5%) were KP-LRTI (OR 1.93; 95% CI 1.25–3.03). Infants with KP-LRTI were younger than those without KP-LRTI (median [IQR] 3.7 [2.1–5.9] vs 4.7 [2.8–7.9] months, P-value=0.009). Clinical features of KP and non-KP-LRTI were similar with 114 (26%) infants hospitalized. Prematurity (adjusted odds ratio [aOR] 11.86; 95% CI 5.22–26.93), HIV exposure (aOR 3.32; 95% CI 1.69–6.53), lower birthweight (aOR 0.68; 95% CI 0.51–0.91), and shorter breastfeeding time (aOR 0.79; 95% CI 0.65–0.96) were associated with KP-LRTI versus non-LRTI. These factors and younger age were associated with KP-LRTI versus non-KP-LRTI. Conclusion: KP was associated with a substantial proportion of LRTI, particularly in premature or HIV-exposed infants in whom strategies for treatment and prevention should be strengthened.